Dreams - 48e Biennale di Venezia, 1999; Aballéa, Martine; Abramović, Marina; Aitken, Doug; Akita, Masami; Ali, Laylah; Althamer, Pawel; Araki, Nobuyoshi; Bachelard, Gaston; Balka, Miroslaw; Bamgboyé, Oladélé; Barney, Matthew; et al. (Torino : Fondazione Sandretto Re Rebaudengo per l'Arte, 1999)
Aballéa, Martine ; Abramovic, Marina ; Aitken, Doug ; Akita Masami ; Ali, Laylah ; Althamer, Pawel ; Araki, Nobuyoshi ; Bachelard, Gaston ; Balka, Miroslaw ; Bamgboyé, Oladélé ; Barney, Matthew ; Beck, Massimo Bartolini ; Berti, Simone ; Bock, John ; Boltanski, Christian ; Bourgeois, Louise ; Briand, Mathieu ; Cai Guo-Qiang ; Cattelan, Maurizio ; Chen Zhen ; Cheong, Wong Hov ; Clancey, William J. ; Windlin, Cornel ; Gu Dexin ; Dono, Heri ; Durham, Jimmie ; Eichhorn, Maria ; Eliasson, Olafur ; Evans, Cerith Wyn ; Fabre, Jan ; Feldmann, Hans-Peter ; Fernández, Teresita ; Fioretos, Aris ; Fischer, Urs ; Framis, Alicia ; Fritsch, Katharina ; Gabellone, Giuseppe ; Garutti, Alberto ; Gaskell, Anna ; Gatev, Dr. ; Gilbert & George ; Gillick, Liam ; Gordon, Douglas ; Grigely, Joseph ; Grimonprez, Johan ; Hausswolff, Carl Michael von ; Hirschhorn, Thomas ; Hirst, Damien ; Hohenbüchler, Christine & Irene ; Höller, Carsten ; Horn, Roni ; Huang Yong Ping ; Hyber, Fabrice ; Ikegami, Takashi ; Janssens, Ann Veronica ; Julien, Isaac ; Kabakov, Ilya & Emilia ; Kentridge, William ; Koo Jeong-a ; Lambri, Luisa ; Latham, John ; Libitsch, Teodolinda von ; Linke, Armin ; Lum, Ken ; Mackie, Christina ; McCarthy, Paul ; McQueen, Steven ; Mekas, Jonas ; Messager, Annette ; Ondreicka, Boris ; Orozco, Gabriel ; Panamarenko ; Pastor, Jennifer ; Pernice, Manfred ; Pettibon, Raymond ; Pistoletto, Michelangelo ; Pivi, Paola ; Pöppel, Ernst ; Prini, Emilio ; Ray, Charles ; Rhoades, Jason ; Rist, Pipilotti ; Rondinone, Ugo ; Rosenfield, Israel ; Sarcevic, Bojan ; Schütte, Thomas ; Shaw, Jim ; Shonibare, Yinka ; Slominski, Andreas ; Sone Yutaka ; Stingel, Rudolf ; Teshigawara, Saburo ; Thorsteinn, Einar ; Tillmans, Wolfgang ; Tiravanija, Rirkrit ; Trockel, Rosemarie ; Tunga ; etc.
This book has been realized on the occasion of the 48e Esposizione Internazionale d'Arte - the Venice Biennial of Visual Arts, 9 - 12 junne 1999
Engels & Frans
kunstcatalogus